Previsão dos preços de commodities por meio das taxas de câmbio - Rosolen, Davi (2013)
This paper aims to model and predict the behavior of commodity prices using theexchange rates of commodity-exporting countries. Understanding commodity pricedynamics is important for a proper control of inflation and planning of production. Ourresults point to a causality relation between the exchange rate and commodity pricesfor all countries under study except South Africa and Argentina. For Australia, Brazil,Canada, Chile, Colombia and New Zealand the exchange rate is an important pieceof information to forecast commodity prices in-sample. For Australia and Canada, thisrelation is also significant out-of-sample. Our results confirm those of Chen, Rogoffand Rossi (2010) and extend that work to the cases of Argentina, Brazil, and Colombia.